(untitled) (Economics and region, 2022)
The peculiarities of the functioning of the European liquefied gas market and its transformation in the conditions of geopolitical challenges in 2022 are considered. The geographical structure of export and import flows of the LNG market in EU countries is considered. It was established that the main active exporters of liquefied gas for European countries are Australia, Qatar, and the USA. Also, Malaysia, Nigeria, Algeria, and Indonesia had significant volumes of deliveries in 2021. It is noted that during 2022, the USA became the main exporter of liquefied gas, more than 70% of which is exported to European countries. Attention is focused on the fact that the European Union is currently the main world exporter of liquefied gas with a potential import volume of more than 150 billion cubic meters per year. Spain, France, Italy, the Netherlands, and Belgium have the largest shares of total liquefied gas imports. An analysis of the features of the implementation of the main infrastructure facilities for LNG import in Germany, Italy, Finland, Croatia, Spain, Poland, and the Netherlands was carried out. The conducted analysis revealed that Spain, France, Germany, the Netherlands, and Italy are the leaders in the import of liquefied gas, on the territory of which LNG terminals are already operating. Cases of construction of LNG terminals in Germany (Lubmin, Wilhelmshaven and Wilhelmshaven ports), Finland (Inkoo port), Finland (Krk island port), Poland (Swinoujscie and Gdańsk ports), the Netherlands (Emshaven port) are presented. It was noted that in parallel with the construction of LNG terminals in the EU countries, a network of gas storage facilities and gas pipelines from the terminals to other EU countries is being actively formed. The conducted analysis revealed that Spain, France, Germany and Italy are the leaders in the import of liquefied gas, on the territory of which LNG terminals are already operating. It is noted that the total number of LNG terminals, which are already functioning or planned in the short term, is 36 terminals. Significant transit prospects for the further transportation of liquefied gas are formed during the construction of LNG terminals in Spain and Poland. However, it was concluded that despite significant qualitative changes in the European liquefied gas market during 2022, the share of Russian energy resources still remains quite significant. Therefore, it is proposed to carry out further transformation of the liquefied gas market of EU countries through further differentiation of importers.